Household energy consumption behaviour for different demographic regions in Thailand from 2000 to 2010 - Tharinya Supasa (2018)
© 2017 by the authors. Since 1995, the residential sector has been a fast-growing energy consumption sector in Thailand. This sector contributes dramatically to the growth of Thailand's electricity and oil demand. Our study analysed Thailand's residential energy consumption charact eristics and the seven underlying factors affecting the growth in energy use of five demographic regions using an energy input-output method. Embodied energy decomposition revealed that direct energy consumption accounted for approximately 30% of total residential energy use, whereas indirect energy consumption was at 70%. During the studied period, the growth in indirect energy use for all household groups was primarily the result of higher consumption of 'commerce', 'air transport', 'manufacturing', 'food and beverages' and 'agriculture' products. Moreover, each influencing driver contributes differently to each household's growth in energy demand. The number of households was the leading factor that dominated the increases in residential energy use in the Greater Bangkok and Central regions. Growth in residential energy consumption in the Northern, Northeastern and Southern regions was strongly dominated by changes in income per capita. Consumption structure and using energy-efficient products had a moderate impact on all regions' energy consumption. Thus, our findings provide additional energy-saving strategies to restrain further growth in residential energy demand.